2015
DOI: 10.1007/s00417-015-3036-9
|View full text |Cite
|
Sign up to set email alerts
|

An extraocular non-invasive transscleral LED-endoilluminator for eye speculum integration

Abstract: A novel LED-endoilluminator which can be attached to a speculum was developed. The system does not need any connection to an external light source and, consequently, also avoids usage of an optical fibre. Regular and uniform illumination of the intraocular space was achieved by transmitted and scattered visible irradiation, avoiding an incision. The duration of potential light exposure, compared to existing illumination systems, can be significantly increased. This is also true when the illuminator is not dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…This illumination by optical fibers is linked with some risks besides infection like photochemical and thermal hazards [3,4] and therefore a more gentle illumination technique was suggested that is based on the idea of transscleral illumination already mentioned by von Graefe in 1868 [5]. In its modern version a white LED is attached to an eye speculum and pressed against the patients eye at the pars plana [6]. The fundus illumination should be achieved transsclerally, which means by light passing through the sclera into the intraocular space.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This illumination by optical fibers is linked with some risks besides infection like photochemical and thermal hazards [3,4] and therefore a more gentle illumination technique was suggested that is based on the idea of transscleral illumination already mentioned by von Graefe in 1868 [5]. In its modern version a white LED is attached to an eye speculum and pressed against the patients eye at the pars plana [6]. The fundus illumination should be achieved transsclerally, which means by light passing through the sclera into the intraocular space.…”
Section: Introductionmentioning
confidence: 99%
“…The fundus illumination should be achieved transsclerally, which means by light passing through the sclera into the intraocular space. This was successfully tested on porcine cadaver eyes [6] but tests on human eyes haveńt been published so far.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 5 illustrates the normalized emission spectrum of the employed LED. The illuminator delivers 1.5 lm luminous flux to the palpebra, which is lower than that of a xenon illumination system for vitreoretinal surgery [13] and the light level of a custom-designed trans-scleral LED illuminator for eye speculum integration [14]. For retinal safety, both photochemical and thermal hazards were considered.…”
mentioning
confidence: 99%